Proteasome dysfunction in Drosophila signals to an Nrf2‐dependent regulatory circuit aiming to restore proteostasis and prevent premature aging. Issue 5 (28th June 2013) - Tsakiri, Eleni N.; Sykiotis, Gerasimos P.; Papassideri, Issidora S.; Terpos, Evangelos; Dimopoulos, Meletios A.; Gorgoulis, Vassilis G.; Bohmann, Dirk; Trougakos, Ioannis P.
Summary: The ubiquitin–proteasome system is central to the regulation of cellular proteostasis. Nevertheless, the impact of in vivo proteasome dysfunction on the proteostasis networks and the aging processes remains poorly understood. We found that RNAi‐mediated knockdown of 20S proteasome subunits in Drosophila melanogaster resulted in larval lethality. We therefore studied the molecular effects of proteasome dysfunction in adult flies by developing a model of dose‐dependent pharmacological proteasome inhibition. Impaired proteasome function promoted several 'old‐age' phenotypes and markedly reduced flies' lifespan. In young somatic tissues and in gonads of all ages, loss of proteasome activity induced higher expression levels and assembly rates of proteasome subunits. Proteasome dysfunction was signaled to the proteostasis network by reactive oxygen species that originated from malfunctioning mitochondria and triggered an Nrf2‐dependent upregulation of the proteasome subunits. RNAi‐mediated Nrf2 knockdown reduced proteasome activities, flies' resistance to stress, as well as longevity. Conversely, inducible activation of Nrf2 in transgenic flies upregulated basal proteasome expression and activity independently of age and conferred resistance to proteotoxic stress. Interestingly, prolonged Nrf2 overexpression reduced longevity, indicating that excessive activation of the proteostasis pathways can be detrimental. Our in vivo studies add new knowledge on the proteotoxic stress‐related regulation of the proteostasis networks in higher metazoans. Proteasome dysfunction triggers the activation of an Nrf2‐dependent tissue‐ and age‐specific regulatory circuit aiming to adjust the cellular proteasome activity according to temporal and/or spatial proteolytic demands. Prolonged deregulation of this proteostasis circuit accelerates aging.